Electronic customer relationship management (E-CRM) features: Comparing two football clubs (Manchester United & Chelsea FC) - Ado, Abdullahi Bala; Hassan, Haslinda; Mohd Nasir, Mohd Herry (2015)
Electronic customer relationship management (e-CRM) is a vital activity of sports marketing that allows building longterm relationship between companies and its customers or fans.This paper examines the content analysis ofthe websites of two football clubs (FC), Manchester United (MU) and Chelsea, focusing specifically on the e-CRM features on the websites. The different use of e-CRM features in both MU and Chelsea FCs are highlighted.The findings demonstrate that both FC teams utilize some of the e-CRM features.